Early Identification and Prognostic Implications in Disseminated Intravascular Coagulation through Transmittance Waveform Analysis - Downey, Colin; Kazmi, Rashid; Toh, Cheng Hock (Thrombosis and Haemostasis, 1998)
Efforts to improve the prognosis in disseminated intravascular coagulation (DIC) have been hampered by the lack of an early, useful and rapidly available diagnostic marker. More recently, a characteristic bi-phasic change in the light transmittance waveform profile of the APTT assay has been associated with DIC. In this prospective study, we have assessed the utility of this assay in the routine clinical setting. 1,470 samples were analysed from 747 patients and 41 patients had DIC. The sensitivity and specificity of the bi-phasic waveform pattern for DIC was 97.6% and 98% respectively. The appearance of a biphasic waveform preceded the development of abnormalities in the standard laboratory tests for DIC and waveform changes correlated closely with clinical events. In conclusion, transmittance waveform analysis is not only useful as an early diagnostic and single monitoring marker of DIC but the quantifiable and standardisable changes also allow for prognostic applicability in clinical management.